2022
DOI: 10.3389/fresc.2022.943397
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical assessment of the ipsilesional upper limb in post-stroke patients during multi-joint reaching tasks: A quantitative study

Abstract: In hemiplegic patients with stroke, investigating the ipsilesional limb may shed light on the upper limb motor control, impairments and mechanisms of functional recovery. Usually investigation of motor impairment and rehabilitative interventions in patients are performed only based on the contralesional limb. Previous studies found that also the ipsilesional limb presents motor deficits, mostly evaluated with clinical scales which could lack of sensibility. To quantitatively evaluate the performance of the ips… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Moreover, recent findings have demonstrated a strong association between the damaged hemisphere and motor control impairments providing that each hemisphere takes part in a different control mechanism for both upper limbs. Studies suggest that ipsilesional upper limb training improves motor coordination and functional performance not only in the trained side but also in the contralesional, increasing participation in ADL [44] . For this reason, we decided to evaluate not only the contralesional side but also the ipsilesional one.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent findings have demonstrated a strong association between the damaged hemisphere and motor control impairments providing that each hemisphere takes part in a different control mechanism for both upper limbs. Studies suggest that ipsilesional upper limb training improves motor coordination and functional performance not only in the trained side but also in the contralesional, increasing participation in ADL [44] . For this reason, we decided to evaluate not only the contralesional side but also the ipsilesional one.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, smoothness measures can be also used for detailed evaluation of motor performance that cannot easily be assessed with clinical scales. For example, the normalized jerk was sensible enough to identify a limited motor performance of the ipsilesional limb in post-stroke patients [37]. Smith et al [38], instead, found that smoothness metrics could detect motor dysfunctions related to Huntington's disease before clinical tests.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, brain-controlled mobiles operate under shared BCI control, which involves combining a BCI system with an intelligent controller. Robots of this type are safer, less tiring for their users, and more accurate in interpreting and executing their commands [71,72]. Therefore, future developments in rehabilitation robotics should enable physicians to choose the most appropriate biomechanical parameters according to an individual patient's specific requirements.…”
Section: Future Perspectives: Combined Approaches and Beyondmentioning
confidence: 99%